Socio-demographic and lifestyle factors associated with dietary patterns among adults with type 3 diabetes mellitus in Tehran, Iran - Zad, Nasrin Darani; Mohd Yusof, Rokiah; Mohseni, Fariba; Jamaluddin, Rosita; Esmaili, Haleh (Medknow Publications, 2015)
This study aimed to assess the dietary patterns among adults with type 2 diabetes mellitus living in Tehran, Iran, and their association with socio-demographic and lifestyle factors. In a cross-sectional study, 400 male and female subjects aged between 40–60 years with type 2 diabetes mellitus were selected. Socio-demographic and lifestyle characteristics and dietary intake were assessed using a food frequency questionnaire. To determine the dietary patterns, factor analysis was carried out, and to assess the association between socio-demographic and lifestyle factors to dietary patterns, analysis of covariance was performed. Three dietary patterns were found. These patterns were labeled as “vegetable and poultry,” “Western” and “mixed.” In this study, the vegetable and poultry pattern was associated with being female, primary education, and hypertension. The Western pattern was associated with being male, non-smokers, and lower physical activity. The mixed pattern was associated with higher income and family history of diabetes. We found that socio-demographic and lifestyle factors of diabetic patients were different according to the dietary pattern type. Further studies are necessary to confirm the benefits of this pattern.